GEN Z WORKFORCE ENGAGEMENT: REDEFINING EMPLOYEE EXPERIENCE THROUGH THE METAVERSE - Herdati, Julia Putri; Rahmawati, Rini (Management Studies and Business Journal (PRODUCTIVITY), 2025)
The development of metaverse technology has changed the dynamics of the work experience, especially for Generation Z who are digital natives. This study aims to explore how the integration of metaverse technology can reshape employee experience and engagement in a virtual work environment.This study focuses on analyzing the impact of metaverse technology on Generation Z's engagement and work experience, taking into account psychosocial and behavioral aspects that are often overlooked in previous literature.This study used a Systematic Literature Review (SLR) approach to identify, evaluate, and synthesize findings from 68 relevant peer-reviewed articles. Data were collected through Scopus and Web of Science databases, and analyzed using thematic analysis techniques.Key findings suggest that elements such as virtual immersion, digital identity, and virtual collaboration significantly increase employees’ emotional and cognitive engagement. Furthermore, the work flexibility offered by the metaverse has the potential to increase job satisfaction, although it also poses the risk of digital fatigue.This study makes an important contribution to employee engagement theory by highlighting the need to integrate digital wellbeing policies into human resource management practices. These findings are expected to serve as a guide for organizations in designing more inclusive and productive work environments.